Pengaruh Strategi Pemasaran, Pemberdayan, dan Pelatihan terhadap Produktifitas Pengrajin kain tapis - Bung Sucinda; Meliyanti Meliyanti; Pramudya M Iqbal Arya; Sanjaya Vicky F (Universitas Ngudi Waluyo, 2021)
The purpose of this study was to see the effect of Marketing Strategy, Empowerment and Training on the productivity of the marketing filter cloth craftsmen. The number of respondents studied was 78 people, using saturated samples. Data collection was done by distributing questionnaires. The analysis technique used is multiple linear regression. The findings in this study are Marketing Strategy, Empowerment and Training have a positive and significant effect on employee work productivity.Keywords: Marketing Strategy, Empowerment, Training, and productivity